QOL-41. FATIGUE AND QUALITY OF LIFE IN CHILDHOOD BRAIN TUMOR AFTER THE END OF TREATMENT. Issue 2 (22nd June 2018) - Profio, Sonia Di; Crocco, Marco; Verrico, Antonio; Milanaccio, Claudia; Iorgi, Natascia Di; Napoli, Flavia; Pacetti, Mattia; Garrè, Maria Luisa
Abstract: PURPOSE: The improvement in survival rates of pediatric patients with brain tumors (BT) has raised questions on the endocrinological, neurocognitive and psychological late effects of long-term survivors. MATERIALS AND METHODS: We retrospectively collected data from 53 children treated at our Institution for BT between 2005-2015 who received psychological and quality of life (QoL) evaluation at a median age of 12.5 years (range, 4.7-18) after a median time of 34 months (range, 1-152) from diagnosis. Data regarding treatment and Neuro-Endocrinological Sequelae (NES): hypothyroidism, hypoadrenalism, hypogonadism, growth hormone deficiency and diabetes insipidus were analyzed. Fatigue was assessed by Facit-F-Peds-Revised (FACIT). QoL was assessed by Pediatric-Quality-of-Life-Inventory. Psychological assessment was carried out using the Child-Behavior-CheckList. RESULTS: Twenty-one patients received neurosurgery, 3 5 patients chemotherapy, 36 patients radiotherapy. Thirty-five patients were NES-free. Four patients developed 1 NES, 12 patients at least 2 NES, 2 patients all 5 NES;t here were no significant differences in terms of FACIT score among these three groups. However the increasing of the number of NES corresponded with worsening of QoL. Fatigue was reported in 25 patients, 7 of them also showed low level of psychosocial and school QoL. The psychological assessment showed clinical levels of emotional distress in 10 children due to increase in anxiety, depression and social problems. CONCLUSIONS: Our preliminary data regarding late effects in childhood BT survivors show that fatigue affects 47% of them. This symptom, not always can be predicted by NES status. QoL was overall good although it worsens with the increase of NES. Further studies will be performed in order to better comprehend the relationship among risk factors and psychosocial outcome.